PREFERENSI MASYARAKAT KECAMATAN PAMIJAHAN DALAM PEMANFAATAN SELF-SERVICE TECHNOLOGIES DIBANK SYARIAH (Studi Pada Kecamatan Pamijahan Kabupaten Bogor, Jawa Barat) - keris kartono; Rully Trihantana; Ria Kusumaningrum (SAHID BANKING JOURNAL, 2021)
Abstract One of the activities of a Sharia Bank that distributes funds to the public to develop a service based on independent information technology to be practical, easy, comfortable, and economical in cost, on Self-Service Technologies (SSTs) services such as Automatic Teller Machines (ATMs), SMS Bankimg, Mobile Banking, and Internet Banking. Currently, people in urban areas have been using SSTs a lot, while in rural areas SSTs the facilities and infrastructure are not sufficient enough. The aim is to examine people's preferences in the use of SSTs in Islamic banks. The research used a descriptive qualitative method with a phenomenological approach, the research subjects were in the Pamijahan sub-district, Bogor regency. The results of this study indicate that people's preferences are like or dislike like the number of respondents who like ATM machines 100% and 0% dislike, Mobile Banking is preferred by 75% and those who do not like it 15%, Internet Banking is preferred by 15% and those who do not like it. 75%, and SMS Banking is preferred 0.5% and 98.05% do not like it. In the village community, Kecamatan Pamijahan prefer ATM machines rather than Mobile Banking, Internet Banking, and SMS Banking because ATM machines are one of the facilities that are characterized by being able to withdraw cash cash at the ATM machine. Utilization of Self-Service Technologies In the Pamijahan sub-district, Bogor Regency, it is time efficient, practical, can check financial 24 hours, is safe, gets bank information, is free to register, and is comfortable. It is necessary to develop SSTs in rural communities so that their use is more optimal. Keywords: Preferences, Utilization of Self-Service Technologies, and Islamic Banks